Implications of the US Cholesterol Guidelines on Eligibility for Statin Therapy in the Community: Comparison of Observed and Predicted Risks in the Framingham Heart Study Offspring Cohort. Issue 4 (April 2015) - Andersson, Charlotte; Enserro, Danielle; Larson, Martin G.; Xanthakis, Vanessa; Vasan, Ramachandran S.
Abstract : Background: Concerns have been raised that the 2013 atherosclerotic cardiovascular disease (ASCVD) risk estimator overpredicts risk in contemporary cohorts. Whether suboptimal calibration will lead to overtreatment with statins is unknown. We investigated the numbers of people eligible for statin treatment in the Framingham Heart Study Offspring Cohort, based on the 2013 cholesterol guidelines, and estimated the proportion that may be overtreated as a result of potential miscalibration of the ASCVD estimator. Methods and Results: During a median follow‐up of 10 years, we observed 285 ASCVD events (8.4%; comprising ischemic stroke, myocardial infarction, and coronary artery disease death) among 3396 men and 112 events (2.9%) among 3838 women. Hosmer–Lemeshow chi‐square statistics were 16.3 in men (340 predicted versus 285 observed events) and 29.1 in women (166 predicted versus 112 observed events). Overprediction predominantly occurred among women in the highest risk decile and among men in the ≥7th risk deciles, for which observed ASCVD event rates were ≥7.5%. In total, 2615 participants (36%; 867 women) were eligible for statins based on the new guidelines. Of these, 171 women (20%) and 154 men (9%) were reclassified downward (as not eligible for statin therapy) using a recalibrated ASCVD estimator. In the latter group, 18 women (10.5%; 95% CI 5.9% to 15.2%) and 11 men (7.1%; 95% CI 3.0% to 11.3%) experienced ASCVD. Conclusions: The risk estimator overpredicted ASCVD risk but did so mainly among high‐risk participants who would be considered eligible for statin use anyway. Our findings may mitigate concerns regarding the potential impact of miscalibration of the ASCVD estimator in contemporary cohorts.